(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
The main objective of this paper is to investigate empirically the validity of DeLone and McLean model in measuring the decision support system success in the banking sector of Oman. Data was collected from decision support system users working in the banks of Oman. Data analysis was done using Structural Equation Modelling (SEM) through smartPLS 2.0. The results of the study showed that system quality and information quality has no influence on system use, system quality and information quality has influence on user satisfaction, system use had no influence on user satisfaction, user satisfaction has no influence on system use, system use had no influence on individual impact, individual impact has no influence on system use, user satisfaction has influence on individual impact and individual impact has influence on user satisfaction.